(untitled) (Revista Iberoamericana de Bioética, 2026)
This paper analyzes the relationship between philosophy and acoustic ecology in El Pedregal de San Ángel Ecological Reserve (REPSA), highlighting the role of sound in understanding the environment. Three philosophical approaches are discussed: phenomenology, which studies the perception of the soundscape; environmental ethics, which defends the value of sound biodiversity; and philosophical aesthetics, which appreciates the beauty of natural sound. Through these approaches, it reflects on the impact of urban noise and the importance of preserving the acoustic balance in urban ecosystems.